2013
DOI: 10.4236/ijcm.2013.43028
|View full text |Cite
|
Sign up to set email alerts
|

Association between Plasma Myeloperoxidase and Free 3-Nitrotyrosine Levels in Patients with Coronary Artery Disease

Abstract: Objective: Myeloperoxidase (MPO) is an inflammatory enzyme that is mainly released by activated neutrophils and monocytes. 3-nitrotyrosine (NT) is a stable inflammatory end product of MPO that is produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Since 3-NT is not a fluorescent compound, it can only be detected using a fluorescence detector after structural modifications, such as the reaction of the amino group of 3-NT with a suitable derivatizing reagent [80]. For instance, Pourfarzam et al [32] used 4-fluoro-7-nitrobenzo-2-oxal,3-diazole (NBD-F) as derivatization reagent. This reagent has been reported in several studies and the results obtained were comparable among them [32].…”
Section: Liquid Chromatography Methods Using Ultraviolet Fluorescencmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 3-NT is not a fluorescent compound, it can only be detected using a fluorescence detector after structural modifications, such as the reaction of the amino group of 3-NT with a suitable derivatizing reagent [80]. For instance, Pourfarzam et al [32] used 4-fluoro-7-nitrobenzo-2-oxal,3-diazole (NBD-F) as derivatization reagent. This reagent has been reported in several studies and the results obtained were comparable among them [32].…”
Section: Liquid Chromatography Methods Using Ultraviolet Fluorescencmentioning
confidence: 99%
“…For instance, Pourfarzam et al [32] used 4-fluoro-7-nitrobenzo-2-oxal,3-diazole (NBD-F) as derivatization reagent. This reagent has been reported in several studies and the results obtained were comparable among them [32]. The fluorescent dyes used in the derivatization step of amino acids significantly improve the sensitivity and specificity of detection.…”
Section: Liquid Chromatography Methods Using Ultraviolet Fluorescencmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides MS-based methods, a wide array of chromatographic, immunochemical, and bio-sensing techniques has been reported to be useful for the identification and quantification of protein Tyr-nitration (recently reviewed in Bandookwala et al, 2020 ). After HPLC, nitrated proteins have been quantified also by UV detection ( Yang et al, 2010 ); by electrochemical detection with sensitivity and selectivity compared to immunodetection methods ( Vujacic-Mirski et al, 2020 ); by fluorescence detection after derivatization ( Pourfarzam et al, 2013 ); and also by photodiode array detection ( Teixeira et al, 2017 ). Size exclusion chromatography coupled to reverse phase-HPLC with diode array detection has been also developed to evaluate protein nitration ( Liu et al, 2017 ).…”
Section: Genetic Code Expansion and Other Methodologies For The Study...mentioning
confidence: 99%
“…The results obtained by the proposed method are agreed with the results of the reference method. The comparison of the proposed photo probe for the determination of 3-nitrotyrosine with other published methods 43–49 is summarized in Table 3. It was revealed that the developed method exhibited good stability, lower limit of detection (8.6 × 10 −10 mol L −1 ) and wide linear range (2.3 × 10 −4 to 1.0 × 10 −9 mol L −1 ).…”
Section: Accuracy and Precisionmentioning
confidence: 99%